DEVELOPMENT OF PROFESSIONAL COMPETENCIES IN TEACHERS: THE ROLE OF TUTOR AND MENTOR: Received: 24th September 2021; Revised: 01st December 2021, 07th March 2022, 15th March 2022; Accepted: 22nd March 2022 - Cramerotti, Sofia (PUPIL: International Journal of Teaching, Education and Learning, 2022)
The purpose of this article is to identify the role played by tutors and mentors in accompanying novice teachers within a specialization course aimed at supporting teachers for the classroom inclusion of students with disabilities. The specific aim of this qualitative research was to investigate the expert teachers’ features and how they (in the role of tutors and mentors) perceive the distinct role they play in the development of novice teachers’ professional competencies through peer review. In particular, the focus was on two different but interconnected activities: a) a direct internship supervised by a tutor; and b) an indirect internship supported by a mentor. Qualitative data were collected through semi-structured interviews with ten expert teachers and were analyzed using a grounded theory approach. Results show a wide proposal of features that characterize a good tutor and mentor in accompanying novice teachers’ growth. Secondly, the collected data provided an important contribution in that they helped identify the most important and useful activities (referring to the direct and indirect internships) for the development of competencies in future support teachers.